2021
DOI: 10.3390/molecules26175353
|View full text |Cite
|
Sign up to set email alerts
|

E-Nose Discrimination of Abnormal Fermentations in Spanish-Style Green Olives

Abstract: Current legislation in Spain indicates that table olives must be free of off-odors and off-flavors and without symptoms of ongoing alteration or abnormal fermentations. In this regard, the International Olive Council (IOC) has developed a protocol for the sensory classification of table olives according to the intensity of the predominantly perceived defect (PPD). An electronic nose (e-nose) was used to assess the abnormal fermentation defects of Spanish-style table olives that were previously classified by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…Regarding the volatile compounds, Californian-style black olives have a characteristic odour of a cooked sensory note [ 15 , 23 , 41 ] that is mainly provoked by the thermal treatment that was used to stabilize these types of olives. Following IOC regulations, the results obtained by these researchers can classify table olives that have been submitted to different sterilization treatments into different sensory categories after considering the predominantly perceived defect (PPD) and intensity attributes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the volatile compounds, Californian-style black olives have a characteristic odour of a cooked sensory note [ 15 , 23 , 41 ] that is mainly provoked by the thermal treatment that was used to stabilize these types of olives. Following IOC regulations, the results obtained by these researchers can classify table olives that have been submitted to different sterilization treatments into different sensory categories after considering the predominantly perceived defect (PPD) and intensity attributes.…”
Section: Discussionmentioning
confidence: 99%
“…This type of sensor matrix has been successfully used for the evaluation of trichloroanisole (TCA) in cork stoppers [ 28 ], air quality measurement [ 29 ], or the discrimination of anomalous fermentation defects in table olives [ 15 ]. The odour profile measurements of the olive and brine samples were carried out following the recommendations of the International Olive Council [ 30 ] for the olive tasting panel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These researchers also found that olive cultivar and sterilization treatment has a significant impact on the amount of cooking defect found due to its relationship with a toxic substance (acrylamide) in Californian-style black olives. 26 Other researchers 27 have argued that electronic noses can be used as olfactory sensors to detect abnormal fermentation (such as zapateria, butyric, putrid, and musty) in table olive defects in order to ensure their quality at industrial level. In this way these results indicated the feasibility of these devices as rapid analytical tools for monitoring the elaboration process of table olives.…”
Section: Quantification Of Sensory Parameters Using An E-nosementioning
confidence: 99%